End-Of-Life Care for Persons with Advanced Chronic Obstructive Pulmonary Disease: Report of a National Interdisciplinary Consensus Meeting. Issue 5 (2009) - Goodridge, DM; Marciniuk, DD; Brooks, D; van Dam, A; Hutchinson, S; Bailey, P; Baxter, S; Dorasamy, P; Dumont, S; Hassan, S; Hernandez, P; Kerigan, A; et al.
Abstract : While systemic shortcomings in meeting the needs of individuals with progressive chronic illnesses at the end of life have been well documented, there is growing interest in improving both care and quality of life for persons with advanced chronic obstructive pulmonary disease (COPD). For instance, the American Thoracic Society has issued an official statement on palliative care for patients with respiratory diseases, affirming that the prevention, relief, reduction and soothing of symptoms "without affecting a cure" must become an integral component of standard care. A recent Medline search located 1015 articles related to palliative or end-of-life care for people with COPD published between 2001 and 2008, compared with only 336 articles published before 2001. To address the needs of Canadian patients, an interdisciplinary consensus meeting, funded by the Canadian Institutes of Health Research and supported by the Canadian Thoracic Society, the Canadian Respiratory Health Professionals and the Canadian Lung Association was convened in Toronto, Ontario, on November 22, 2008, to begin examining the quality of end-of-life care for individuals with COPD in Canada. The present report summarizes the background to and outcomes of this consensus meeting.